THE RELATION OF STRUCTURE TO THE GAS SEEPAGE OCCURRENCE - BINTI WAN ISMAIL, WAN NURSYAZANA SYARAH (Universiti Teknologi PETRONAS, 2015)
In oil and gas industry, seismic data is one of the fundamental data in hydrocarbon exploration. The jobs of seismic interpreters are meaningful to the industry. Good interpretation will lead to meaningful information. However, there are some challenges in interpreting the seismic section. One of the challenges is the existence of gas cloud in the subsurface. Gas cloud gives blurry and chaotic image in seismic section which prevents geophysicist from seeing the geological image behind the gas cloud. Gas cloud can also be related to fractures in the structure which allows gas to migrate upwards through the fractures and causes the blurry image in the seismic section. Therefore, to get better understanding on the fractured area, a geological field work was held to study the characteristic of fractured structure and how was it affected by stress force. Other elements considered are the clastic sediments and age of the rock. Strong understanding in the geological view enhances our fundamental knowledge of the study and further aid in seismic work and interpretation. Stress effect to the Seri Iskandar Outcrops were studied by taking strike and dip measurements of the fractures and transfer the readings into a rose diagram for each outcrop. A 3D seismic section of Sepat Field is then studied and interpreted. After dividing the seismic data into seismic units by horizon interpretation, the structural geology of the field is then studied and interpreted. A number of fractures and faults are identified at the gas cloud zone as well as gas seepage. From the literature review of Malay Basin tectonic history and seismic interpretation done, it is concluded that fractures and faults may create the migration path for the gas seepage occurrence in Sepat Field.